2012
DOI: 10.1148/radiol.11110601
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Multiple Sclerosis Lesions: Characterization with High-Field-Strength MR Imaging

Abstract: Purpose:To elucidate the mechanism of magnetic resonance (MR) imaging contrast in multiple sclerosis (MS) lesion appearance by using susceptibility-weighted imaging and to assess with histologic correlation the role of iron and myelin in generating this MR imaging contrast. Materials and Methods:Each patient provided written consent to a human subject protocol approved by an institutional review board. Highspatial-resolution susceptibility-weighted 7.0-T MR images were obtained in 21 patients with MS. Contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
124
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(138 citation statements)
references
References 38 publications
7
124
2
2
Order By: Relevance
“…One postmortem study that did look at T2*WI sensitivity showed a 48% prospective sensitivity but made no distinction among lesion types. 12 Another 7T study found that 46% of cortical lesions could be prospectively detected by using T2*WI and a similar 43% could be detected by using a WMattenuated turbo field echo. 13 However, the 2 sequences studied were suboptimally matched in terms of image resolution, which may explain the relative absence of differences between them.…”
mentioning
confidence: 94%
“…One postmortem study that did look at T2*WI sensitivity showed a 48% prospective sensitivity but made no distinction among lesion types. 12 Another 7T study found that 46% of cortical lesions could be prospectively detected by using T2*WI and a similar 43% could be detected by using a WMattenuated turbo field echo. 13 However, the 2 sequences studied were suboptimally matched in terms of image resolution, which may explain the relative absence of differences between them.…”
mentioning
confidence: 94%
“…Recent studies have confirmed histologically that WM-SAs visible on MR imaging phase and R 2* correspond to focal iron deposits, whereas T2 and T1 WM-SAs are influenced by water content. 11 A substantial subset of MS WM-SAs has phase shifts 11,12 and morphologic differences. [11][12][13][14][15] However, factors other than nonheme iron may influence the observed WM-SA signal, such as changes in myelin, deoxyhemoglobin, and inflammation.…”
mentioning
confidence: 99%
“…11 A substantial subset of MS WM-SAs has phase shifts 11,12 and morphologic differences. [11][12][13][14][15] However, factors other than nonheme iron may influence the observed WM-SA signal, such as changes in myelin, deoxyhemoglobin, and inflammation. 11,[16][17][18][19] Therefore, because there are a multitude of effects, it is not fully known to what extent they each individually influence SWI-filtered phase changes.…”
mentioning
confidence: 99%
See 2 more Smart Citations